2006
DOI: 10.1210/jc.2006-0328
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Term Calorie Restriction with Adequate Protein and Micronutrients on Thyroid Hormones

Abstract: Long-term CR with adequate protein and micronutrient intake in lean and weight-stable healthy humans is associated with a sustained reduction in serum T(3) concentration, similar to that found in CR rodents and monkeys. This effect is likely due to CR itself, rather than to a decrease in body fat mass, and could be involved in slowing the rate of aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
97
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(110 citation statements)
references
References 20 publications
9
97
2
2
Order By: Relevance
“…Despite a similar body mass index (10,12) or fat content (11), long-term calorie restriction and exercise resulted in disparate effects on various parameters related to aging, including thyroid function, systemic inflammation, and growth factors. For instance, individuals engaged in voluntary calorie restriction were found to have lower levels of serum T 3 and TNF-␣ levels than exercisers or a control group consuming a typical Western diet (11). In another study, individuals consuming a low calorie-low protein diet were shown to have a more favorable cancer risk profile than endurance runners or controls, including lower serum IGF-1 and greater levels of dehydroepiandrosterone sulfate and sex-hormone-binding globulin (10).…”
Section: Discussionmentioning
confidence: 99%
“…Despite a similar body mass index (10,12) or fat content (11), long-term calorie restriction and exercise resulted in disparate effects on various parameters related to aging, including thyroid function, systemic inflammation, and growth factors. For instance, individuals engaged in voluntary calorie restriction were found to have lower levels of serum T 3 and TNF-␣ levels than exercisers or a control group consuming a typical Western diet (11). In another study, individuals consuming a low calorie-low protein diet were shown to have a more favorable cancer risk profile than endurance runners or controls, including lower serum IGF-1 and greater levels of dehydroepiandrosterone sulfate and sex-hormone-binding globulin (10).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast outer ring deiodination by types 1 and 2 deiodinases leads to activation of T 4 into T 3 (20,21). Clinical studies illustrated that rT 3 serum concentrations increase with age (1,12,13), the presence of multiple diseases (12), and may be influenced by energy intake (despite conflicting results) (13,22). However, whether these variations should be taken into account is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…low plasma levels of thyroid hormones is associated with abnormal menstrual cycles and disrupted follicular development (Ortega et al, 1990;Vriend et al, 1987). From experimental data it appears that in response to protracted CR there is a decrease in serum T 3 concentrations but little change in T 4 (Roth et al, 2002;Fontana et al, 2006). The effect of CR upon TSH however seems quite subtle as there appears to be little change in TSH levels during acute CR, but with long-term CR TSH levels may be elevated (Roth et al, 2002).…”
Section: Thyroid Hormonementioning
confidence: 99%